Airports, the challenging future proceedings of the 5th World Airports Conference on technological and economic change, 5-7 May, 1976 - Monro, Mary (Institution of Civil Engineers, 1976)
Topics covered in these papers include the demand for air transport, national airport planning, maximizing airport use, environmental considerations, functional requirements, designs for new airports in developing countries, ground facilities and keeping the aiport in service. Sir Peter Masefield provides a closing address.